Firm size, managerial practices and innovativeness: Some evidence from Finnish manufacturing - Heli Koski; Luigi Marengo; Iiro Mäkinen (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2009)
In this study we use a survey data on 398 Finnish manufacturing firms for the years 2002 and 2005 to empirically explore whether and which organizational factors explain why certain firms produce larger innovative research output than others, and whether the incentives to innovate that certain organizational practices generate differ between small and large firms, and between those firms that are operating in low-tech and high-tech industries. Our study indicates that there appear to be vast differences in the organizational practices leading to more innovation both between small and large firms, and between the firms that operate in high- and low-tech industries. While innovation in small firms benefits from the practices that enhance employee participation in decision-making, large firms that have more decentralized decision-making patterns do not seem to innovate more than those with a more bureaucratic decision-making structure. The most efficient incentive for innovation among the sampled companies seems to be the ownership of a firm's stocks by employees and/or managers. Performance based wages also relates positively to innovation, but only when it is combined with a systematic monitoring of the firm's performance.
Keywords: L25; M54; O31; 330; innovation; firm size; organizational practices; HRM practices